Pengaruh Kompensasi Finansial dan Lingkungan Kerja Nonfisik Terhadap Kepuasan Kerja Karyawan PT. Hirfi Studio - Realita, Wanda Sofiatul Fauziah , Tasnim Nikmatullah; Anggoro, Yudhi (STIE AMKOP, 2024)
This study examines the impact of financial compensation and non-physical work environtment on employee job satisfaction at PT Hirfi Studio, a consulting firm in the transportation sector. Financial compensation, which includes salaries bonuses, allowances ada incentives is considered crucial for retaining skilled employees facing technical challenges and tight deadlines. A supportives non-physical work environtment, characterized by good relationship with supervisors anda colleagues, workplace culture, as well as recognition and rewards, can enhance job satisfaction. This research employed a quantitative method with a saturated sample of 70 employees, with data collected through questionnaires and interviews. The findings indicate that financial compensation does not affect job satisfaction, whereas the non-physical work environtment significantly influences employee satisfaction. Nonetheless, both independent variables, financial compensation and non-physical work invirontment, simultaneously have a significant effect on employee job satisfaction. The result underscore the importance of fair compensation and a positive work asmosphere in supporting employee productivity and work quality. Keywords: Financial compensation, non-physical work environtment, employee job satisfaction